Establishment of reverse genetics system for infectious bronchitis virus attenuated vaccine strain H120 - Zhou, Ying Shun (Vet Microbiol, 2013)
Infectious bronchitis virus (IBV) strain H120 was successfully rescued as infectious clone by reverse genetics. Thirteen 1.5–2.8 kb fragments contiguously spanning the virus genome were amplified and cloned into pMD19-T. Transcription grade complete length cDNA was acquired by a modified “No See’m” ligation strategy, which employed restriction enzyme Bsa I and BsmB I and ligated more than two fragments in one T4 ligase reaction. The full-length genomic cDNA was transcribed and its transcript was transfected by electroporation into BHK-21 together with the transcript of nucleocapsid gene. At 48 h post transfection, the medium to culture the transfected BHK-21 cells was harvested and inoculated into 10-days old SPF embryonated chicken eggs (ECE) to replicate the rescued virus. After passage of the virus in ECE five times, the rescued H120 virus (R-H120) was successfully recovered. R-H120 was subsequently identified to possess the introduced silent mutation site in its genome. Some biological characteristics of R-H120 such as growth curve, EID50 and HA titers, were tested and all of them were very similar to its parent strain H120. In addition, both R-H120 and H120 induced a comparable titer of HA inhibition (HI) antibody in immunized chickens and also provided up to 85% of immune protection to the chickens that were challenged with Mass41 IBV strain. The present study demonstrated that construction of infectious clone from IBV vaccine strain H120 is possible and IBV-H120 can be use as a vaccine vector for the development of novel vaccines through molecular recombination and the modified reverse genetics approach.